2019
DOI: 10.1162/jinh_a_01377
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic Uncertainty, Subjective Probability, and Ancient History

Abstract: The subjective interpretation of probability—increasingly influential in other fields—makes probability a useful tool of historical analysis. It provides a framework that can accommodate the significant epistemic uncertainty involved in estimating historical quantities, especially (but not only) regarding periods for which we have limited data. Conceptualizing uncertainty in terms of probability distributions is a useful discipline because it forces historians to consider the degree of uncertainty as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…A more defensible and productive epistemic stance could be to understand historical research as Bayesian abductive inference -that is, a probabilistic reasoning from effects to causes, or more specifically from the traces left by the past, including physical and written records, to hypotheses about the past itself. Previous studies have demonstrated that this stance encapsulates the implicit principles underlying historical research, and that consciously adopting Bayesian abductive methods improves the accuracy of historical studies and communication (Tucker, 2004;Lavan, 2019). Our study instantiates this epistemological shift in the interdisciplinary field of historical climatology.…”
Section: Discussionsupporting
confidence: 55%
“…A more defensible and productive epistemic stance could be to understand historical research as Bayesian abductive inference -that is, a probabilistic reasoning from effects to causes, or more specifically from the traces left by the past, including physical and written records, to hypotheses about the past itself. Previous studies have demonstrated that this stance encapsulates the implicit principles underlying historical research, and that consciously adopting Bayesian abductive methods improves the accuracy of historical studies and communication (Tucker, 2004;Lavan, 2019). Our study instantiates this epistemological shift in the interdisciplinary field of historical climatology.…”
Section: Discussionsupporting
confidence: 55%
“…362-363). These issues become an important point of contrast with an approach such as that taken by Myles Lavin [16] who advocates very strongly for adopting a statistical approach to the epistemic uncertainty of history. His argument does, in many ways, bring out some of the same sorts of weaknesses in the historical research process as Blau does, in particular the nature of the historical evidence base, the lack of a stable language for describing levels and types of uncertainty, and the possibility for overconfidence and anchoring in previous work to lead to the propagation of conclusions based upon earlier flawed interpretations.…”
Section: Motivations and Mechanisms For Managing Uncertaintymentioning
confidence: 99%
“…Even if we take his understanding of the nature of the uncertainty in question here as valid (the discussion of quantities versus events, for example, seems particularly tentative [16] (p. 99), the process by which probabilities could be assigned to the range of interpretations available seems merely to take the process of weighing and considering, which Blau sought to make transparent, and displace it to a quantifiable space within a compounded Bayesian black box. This is perhaps not the intention, for, as he explains, "It becomes much easier if we remind ourselves that probability curves 'do not exist,' as De Finetti said, "They are only a language in which we express our state of knowledge or state of certainty" [16] (p. 103), but given that this is the case, it would seem that Blau's strategy of maintaining the complexity and the provenance of the arguments being made would be an ultimately more productive one, in particular as the assignment and accretion of probabilities does not remove the reliance upon potentially flawed assumptions from the process: "Even in fields with much better data, estimation often entails an irreducible element of subjective judgment" [16] (p. 102). In particular the proposition that "A traditional point estimate based on most-likely values for each of the input quantities could never hope to command credibility because of the proliferating uncertainties" [16] (p. 106) seems rather overextended, given that authority in historical research has indeed been constructed for many centuries now without recourse to probabilities.…”
Section: Motivations and Mechanisms For Managing Uncertaintymentioning
confidence: 99%
“…Buck et al 1996 is a more formal presentation aimed at archaeologists. The idea of using subjective probabilities to represent epistemic uncertainty in history is discussed briefly in Lavan 2016 and in more detail in Lavan 2019a.…”
mentioning
confidence: 99%